Analogue discovery of safer alternatives to HCQ and CQ drugs for SAR-CoV-2 by computational design. (March 2021) - Sinha, Meetali; Gupta, Anshika; Gupta, Shristee; Singh, Prakrity; Pandit, Shraddha; Chauhan, Shweta Singh; Parthasarathi, Ramakrishnan
Abstract: COVID-19 outbreak poses a severe health emergency to the global community. Due to availability of limited data, the selection of an effective treatment is a challenge. Hydroxychloroquine (HCQ), a chloroquine (CQ) derivative administered for malaria and autoimmune diseases, has been shown to be effective against both Severe Acute Respiratory Syndrome (SARS-CoV-1) and SARS-CoV-2. Apart from the known adverse effects of these drugs, recently the use of CQ and HCQ as a potential treatment for COVID-19 is under flux globally. In this study, we focused on identifying a more potent analogue of HCQ and CQ against the spike protein of SAR-CoV-2 that can act as an effective antiviral agent for COVID-19 treatment. Systematic pharmacokinetics, drug-likeness, basicity predictions, virtual screening and molecular dynamics analysis (200 ns) were carried out to predict the inhibition potential of the analogous compounds on the spike protein. This work identifies the six potential analogues, out of which two compounds, namely 1-[1-(6-Chloroquinolin-4-yl) piperidin-4-yl]piperidin-3-ol and (1R, 2R)-2-N-(7-Chloroquinolin-4-yl)cyclohexane-1, 2-diamine interact with the active site of the spike protein similar to HCQ and CQ respectively with augmented safety profile. Graphical abstract: Image 1 Highlights: COVID-19 outbreak poses a severe health emergency to the global community. Hydroxychloroquine (HCQ) has been shown to be effective against both SARS-CoV-1 and SARS-CoV-2. Analogues of HCQ and chloroquine were screened using multiresolution computational framework for antiviral drug discovery. Six analogues were identified as potential spike protein inhibitors with augmented safety profile.